Robot-assisted Laparoscopic Pyeloplasty in Adults: A Comparison Analysis of Primary versus Redo Pyeloplasty in a Single Center - Dirie, Najib Isse; Ahmed, Mahad A; Mohamed, Mohamed Abdulkadir; Zhang, Zongbiao; Wang, Shaogang (Urology Journal, 2020)
Purpose: Approximately 10% of all primary pyeloplasties will require at least one secondary intervention. Our aim was to analyze whether secondary repair will pose additional challenges during robotic pyeloplasty compared with the primary pyeloplasty. Material and Methods: 114 patients who underwent robot-assisted laparoscopic pyeloplasty (RALP) between February 2015 and August 2018 were retrospectively reviewed. Patients were divided into; primary and secondary repair. The demographics, intraoperative parameters, postoperative parameters, and success rate of these two groups were collected and compared. Primary RALP data were further stratified into those who previously underwent ipsilateral endourological surgeries (IES) at the obstruction site and those who did not, to evaluate the effect of IES has on the outcome of RALP. Success was defined as symptomatic and radiological relief. Results: Of the 114 patients, five complicated cases (three horseshoe kidneys, one duplicated system, and one retrocaval ureter) were excluded from the comparison. The remaining 96 primary and 13 secondary repairs were compared. Intraoperative and postoperative parameters showed no significant difference between the two groups. The results of 99 patients (87 vs. 12 in primary vs. secondary, respectively) were available after 27.5 months mean follow-up. The overall success was 92%, 8 patients failed (5 vs. 3 in primary vs. secondary, respectively) and required further surgical interventions. Conclusion: Though surgically challenging with increased recurrence rates according to the literature we reviewed. However, our data failed to show any significant difference between the primary and redo RALP perhaps due to the smaller size in the redo RALP group.